Study of characteristics of rice husk and silica obtained from rice husk - Zainal, Nur Saadah; Mohamad, Zaleha; Mustapa, Mohammad Sukri; Badarulzaman, Nur Azam; Abdul Salim, Zainathul Akhmar Salim; Masirin, Mohd Idrus (IACSIT Press, 2018)
This paper presents the study of the features of the rice husk and to investigate the presence of silica in the rice husk. To obtain the pure silica, the rice husk was firstly washed and went through chemical treatment, prior to combustion. The combustion process was conducted at temperature of 700℃ for 2 hours. The rice husk ash obtained was studied and has been named as C3. The characteristics of C3 samples can be acquired by using scanning electron microscopy (SEM), x-ray diffractometer (XRD) and thermogravimetric analysis (TGA). The SEM images showed the material was in agglomeration. The silica content of C3 was observed to be 89.85% using EDS. The thermal properties of the C3 also was performed using TGA as the change with temperature up to 1000℃ with heating rate of 5℃/min. As from the result, the energy of organic compound lose at 700℃ was 0.0141mg/min and at 1000℃ was 0.00217 mg/min.